From Cheating to Cheat Codes: Integrating Generative AI Ethics into Collaborative Learning. - Girdharry, Kristi (College Composition & Communication, 2025)
In gaming, cheat codes change how players engage a system by inviting exploration and reducing the fear of failure. Drawing on writing center pedagogy, this article proposes a similar framework for navigating generative AI in writing instruction and positions play as a method for developing critical AI literacy. Writing centers have long served as spaces where students engage collaboratively with new technologies and construct meaning through dialogue. This article extends that tradition by positioning writing center pedagogy as a framework for helping students examine AI's ethical implications through treating it as a rhetorical situation to be unpacked, which demands principled, human-centered engagement rooted in values such as collaborative exploration. By weaving together writing center praxis and game-informed pedagogy, this article contributes to ongoing conversations in writing studies about how to integrate AI in ways that support critical thinking and ethical reflection. It demonstrates how playful, classroom-tested activities can animate discussions of bias and representation while helping students build rhetorical discernment through experience. Ultimately, the article argues that ethical literacy must be practiced through relational, iterative work. As writing classrooms become one of the few remaining spaces where students encounter generative AI with support and critical context, writing instructors have a vital opportunity to help students learn to write with, against, and around powerful technologies.